Tren Topik Penelitian dan Kajian Bibliometrik Prosiding Bidang Ilmu Perpustakaan di Indonesia Periode 2015-2017 - Dwiyantoro Dwiyantoro; Sri Junandi (Media Pustakawan, 2019)
Introduction, this study is discussing trends in research topics in the field of library science and information and looking at bibliometric studies. Research and Analysis Methods, The method in this study is bibliometrics with Co-Word analysis methods and citation analysis. First, word analysis is done to look at research trends by grouping keywords, then grouping them according to Hawkins' taxonomy. Second, the citation analysis is done by looking at the bibliography to see the types of literature, literature, and obsolescence literature.The results and discussion, the trend of research topics in the library scientific field that developed in the 2015-2017 period were library and library services and social problems, while the results of citations analysis showed the type of literature most widely used by book literature (53, 49%) and journals (9.65%). The most literary languages are Indonesian (61.08%) and English (38.00%), while the age of documents cited is still relevant, namely 0-10 years (63.82%) and 0-20 years (28 , 67%). Conclusions, Trends in further research topics on the topic of Libraries and Library Services and Social Issues, there is a diversity of types of literature cited, available diversity of languages and the level of obsolescence of documents cited.